Animal transgenesis now and beyond in the era of genome editing: Snapshots from the 15th Transgenic Technology Meeting (TT2019) in Kobe, Japan. (8th November 2019) - Kiyonari, Hiroshi; Furuta, Yasuhide
Abstract: The 15th Transgenic Technology (TT) Meeting of the International Society for Transgenic Technologies (ISTT) was held for the first time in Japan in April of 2019 (TT2019). Delegates from around the world, including researchers, technicians and trainees, spent an exciting 4 days, engaging in scientific and technical discussions, information sharing and networking. In the era of genome editing, CRISPR technologies prevailed as popular subjects of discussion throughout the meeting on topics ranging from their applications in the mouse and growing number of other research and industrial animal species, technical challenges in the production of genome‐edited animals, to ethical considerations in biomedical research. In particular, impressive progress was reported on the use of CRISPR technologies in nonconventional animal models and large mammalian species in biomedical and industrial settings, indicating areas of expanding frontiers in animal transgenesis. Amid growing excitement with genome editing technologies, reports on conventional genetic engineering approaches and reproductive biology techniques demonstrated that these techniques remain essential to meet the demanding needs of generating complex genome modifications, complementing genome editing approaches. TT2019 was a great success, concluding with a widely shared appreciation of the current field and hints for future directions of animal transgenesis. Abstract : A meeting report for the 15th Transgenic Technology Meeting (TT2019) of the International Society for Transgenic Technologies held on April 7th to 10th, 2019, in Kobe, Japan.